Deformation Responses and Mechanical Mechanism of Existing Tunnel due to New Building Construction - Haifeng Guo; Dong Ma; Aijun Yao (Advances in Civil Engineering, 2021)
This study mainly investigated the variation law and mechanical mechanism of surrounding earth pressure and deformation of an existing tunnel, caused by dewatering, foundation excavation, building loading, and groundwater recovery. According to different dewatering schemes, two modes were established: nonisolated dewatering unloading-loading mode and isolated dewatering unloading-loading mode. Through large-scale similar materials model test, the variation law of deformation and surrounding earth pressure of adjacent tunnel under complex unloading-loading conditions was preliminarily revealed. Based on the size of the prototype project, the test results were further verified by the numerical simulation. The mechanical mechanism of tunnel deformation in different construction stages was analyzed after the comparative study. The results show that the tunnel structure deformation, vertical and horizontal displacement, and torsion occur in the process of building construction. In the nonisolated dewatering unloading-loading mode, the decrease or rise of the groundwater level significantly reduces (maximum 27.85%) or increases (maximum 35.19%) the surrounding earth pressure of the tunnel. The decrease or increase of the horizontal total stress was much greater than that of the vertical total stress, which leads to the deformation of tunnel structure. The vertical displacement of the tunnel is generally settlement, which mainly occurs in the stage of dewatering and building loading, accounting for 83.21%–100.00% and 25.11%–40.34% of the total settlement, respectively. In the stage of foundation pit excavation and groundwater recovery, the tunnel rises. In the horizontal direction, the tunnel moves towards the foundation pit, mainly in the excavation stage, accounting for 82.77%–86.30% of the maximum value. Due to the uneven change of displacement field and stress field of soil outside the foundation pit, the tunnel torsion occurs. In the isolated dewatering unloading-Loading mode, the change of groundwater has little effect on the tunnel. In the stage of excavation and construction load, the variation law of tunnel surrounding earth pressure and deformation is similar in the two modes.